-5x-3x+9x=4-x

Simple and best practice solution for -5x-3x+9x=4-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-3x+9x=4-x equation:


Simplifying
-5x + -3x + 9x = 4 + -1x

Combine like terms: -5x + -3x = -8x
-8x + 9x = 4 + -1x

Combine like terms: -8x + 9x = 1x
1x = 4 + -1x

Solving
1x = 4 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
1x + x = 4 + -1x + x

Combine like terms: 1x + x = 2x
2x = 4 + -1x + x

Combine like terms: -1x + x = 0
2x = 4 + 0
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 1/2x=1/4-6 | | w/7=3=-1 | | 2(2-5x)=8x-2 | | 13=-10y+3y | | 4(x-3)(x+4)=0 | | 5y-y=-12+y | | 2.5=(x-54166)/10200 | | 4(5x-3)+9=-2 | | (6x+2)(7x^2-5x-4)= | | 2x-10=38 | | -9r+1=-80 | | 3x8/3 | | mx^2+(2m-1)x+(m-1)=0 | | 5=x/4=1 | | 16=-10b+3b | | x^3-5x=-3 | | -8x-8=9x+43 | | 8(y-1)+5(y-1)= | | 5x+9y=-42 | | 2(x+6)-4(-x+3)=3(2x+1)-3 | | 2b*b*3a= | | -3x+2y=-34 | | -8(-x)-4(x-2)=8 | | 3S+45=10 | | 4(y-3)+3=8(2y+5) | | (3x-2y)+8=-15 | | 3x+6(-1)=-30 | | -1x+14= | | 3x^4+x^3+3x^2-29x-10=0 | | 5w+-2.5=-7.5 | | g-2=1/4(4g-2) | | 2B+40=240 |

Equations solver categories